Guidelines for Enhancing the Success of Online Learning for Undergraduate Students at the Faculty of Education, Ramkhamhaeng University - Tippayakulpairoj, Darunee (Journal of Education Studies, Chulalongkorn University, 2023)
Instructors in higher education increasingly use technologies for instruction; therefore, undergraduate students are able to access and engage in online learning more conveniently. This study was divided into two phases; the first phase consisted of an analysis of the online learning characteristics of undergraduate students and validation of the causal model for the online learning success of undergraduate students. A total of 607 undergraduate students who studied in the Faculty of Education at Ramkhamhaeng University were selected through stratified random sampling according to year level. The research instrument employed was a questionnaire, and data were analyzed using descriptive statistics, one-way ANOVA, and structural equation model analysis. The second phase involved developing guidelines for enhancing the online learning success of undergraduate students. Teachers and undergraduate students selected through purposive selection were interviewed, and data were analyzed through content analysis. The results were as follows: Students who reviewed online course materials for 5-10 hours and 11-15 hours per week had significantly higher grades than those who spent less than 5 hours per week. The causal model of online learning success fit with the empirical data ((40, N=607) = 53.78, p = .07, CFI = 0.99, RMSEA = 0.02, SRMR= 0.01). The guidelines for enhancing the online learning success of undergraduate students in the Faculty of Education at Ramkhamhaeng University were presented in three parts: the course design of the instructors, the characteristics of the undergraduate students, and university support.